Moderate hypothermia during ex vivo machine perfusion promotes recovery of hearts donated after cardiocirculatory death† - Tolboom, Herman; Olejníčková, Veronika; Reser, Diana; Rosser, Barbara; Wilhelm, Markus J; Gassmann, Max; Bogdanova, Anna; Falk, Volkmar (European journal of cardio-thoracic surgery, 2016)
OBJECTIVES: To establish the optimal machine perfusion temperature for recovery of hearts in a rodent model of donation after declaration of cardiocirculatory death (DCD). METHODS: Hearts from male Lewis rats (n = 14/group) were subjected to 25 min of in situ warm (37°C) ischaemia to simulate DCD. They were then explanted and reperfused with diluted autologous blood for 60 min at 20, 25, 30, 33 or 37°C, after which they were stored at 0-4°C in Custodiol preservation solution for 240 min. Fresh-excised and cold-stored ischaemic hearts were used as controls. The viability of the different groups was assessed by comparing heart rate and left ventricular contractility in a Langendorff circuit, as well as perfusate levels of troponin-t and creatine kinase (CK), and myocardial levels of adenosine triphosphate (ATP) and reduced glutathione. RESULTS: During ex vivo reperfusion, hearts in all groups resumed beating within minutes. The mean heart rate was highest in the 37°C group at 154.72 ± 33.01 beats × min(-1) (bpm), and declined in proportion to temperature to 39.72 ± 5.53 bpm at 20°C. Troponin-t levels were highest in the 37°C group (79.49 ± 20.79 µg/l), the values were significantly lower in all other reconditioned groups with a minimum of 12.472 ± 7.08 µg/l in the 20°C group (P < 0.0001). Tissue ATP levels ranged from 4.32 ± 1.71 µmol/g at 33°C to 4.59 ± 1.41 µmol/g at 30°C, all significantly higher than the mean ATP level of 1.41 ± 0.93 µmol/g in untreated ischaemic hearts (P < 0.0001). During Langendorff assessment, the mean heart rate and contractility of all groups were higher than those of cold-stored ischaemic hearts (P < 0.0001), yet not significantly different from those of fresh controls. The perfusate levels of troponin-t and CK, and myocardial levels of reduced-glutathione and ATP were not significantly different between groups. CONCLUSION: Our results suggest that mild hypothermia during ex vivo reperfusion improves recovery of ischaemic hearts in a rodent DCD model.
Keywords: reperfuze myokardu; transplantace srdce; dárci tkání; Recovery of Function; Graft Survival; obnova funkce; potkani inbrední LEW; míra přežití; náhodné rozdělení; Cold Ischemia; Rats; zvířata; Animals; Death; Male; Tissue and Organ Harvesting; Random Allocation; Rats, Inbred Lew; studená ischemie; smrt; Tissue Donors; Heart Transplantation; mužské pohlaví; Survival Rate; techniky in vitro; Organ Preservation; Disease Models, Animal; uchovávání orgánů; terapeutická hypotermie; Hypothermia, Induced; modely nemocí na zvířatech; přežívání štěpu; In Vitro Techniques; krysa rodu Rattus; odběr tkání a orgánů; Myocardial Reperfusion